Nano Zinc Oxide and Prosopis farcta Against Cotton Seed Bug: Nano Oksida Seng dan Prosopis farcta terhadap Hama Biji Kapas - Majida Mohammad Abid Falhy; Zahraa Falah Azeez (Indonesian Journal on Health Science and Medicine, 2025)
General Background Nanotechnology has gained increasing attention as an alternative strategy for insect pest management. Specific Background Zinc oxide nanoparticles and plant-derived extracts have been reported as promising bio-based agents against agricultural pests. Knowledge Gap However, limited studies have evaluated green-synthesized zinc oxide nanoparticles derived from Prosopis farcta fruits against cotton seed bug populations under local Iraqi conditions. Aims This study aimed to synthesize zinc oxide nanoparticles using an alcoholic extract of Prosopis farcta fruits and assess their biological activity against immature and adult stages of Oxycarenus hyalinipennis under laboratory conditions. Results The alcoholic fruit extract showed the highest mortality, reaching 90.00% within 24 hours at 2000 ppm, followed by biosynthesized zinc oxide nanoparticles, while pure zinc oxide nanoparticles produced lower mortality rates. Characterization confirmed successful nanoparticle synthesis with nanoscale dimensions and distinct morphological features. Novelty This research demonstrates the use of Prosopis farcta fruit extract as a dual reducing and stabilizing agent for zinc oxide nanoparticle synthesis with insecticidal properties. Implications The findings support the potential application of plant-based nanomaterials as alternative tools for sustainable pest management programs. Keywords: Zinc Oxide Nanoparticles, Prosopis Farcta, Green Synthesis, Oxycarenus Hyalinipennis, Pest Control Key Findings Highlights: Alcoholic fruit extract produced the highest mortality within 24 hours. Biosynthesized particles showed stronger activity than commercial material. Early developmental stages were more susceptible than later stages.